Difficulties in the Use of Bill of Lading in Norilsk Nickel Harjavalta Oy - Tasku, Eeva (Satakunnan ammattikorkeakoulu, 2012)
The purpose of this thesis was to study the difficulties related to a sea transportation document called bill of lading. The study was implemented on behalf of a company called Norilsk Nickel Harjavalta Ltd, which is a large international company operat-ing in the metal industry. The case company wanted me to find out if there were some ways to decrease the difficulties related to the use of bills of lading and espe-cially to bill of lading drafts. Norilsk Nickel had had problems with bill of lading drafts for quite some time, and the company felt that it was time to solve the difficul-ties as they caused additional work and consequently extra costs. My task was to of-fer the company different ways to manage and solve the difficulties. I chose this topic because Norilsk Nickel offered this topic to me while I was doing my practical training in the company. I had noticed the same difficulties with bills of lading through my work and I had great interest to the subject. I wanted to learn more about bills of lading and at the same time help my colleagues and the company with the problems. These difficulties took time and resources from a number of parties and the case company needed solutions that would decrease the amount of work. This study was implemented as a qualitative research. In the theory section I have examined common exporting documents and bills of lading in general and in addition to this, I have presented different kinds of bills of lading and their use. The in-formation on the theory is gathered from books, the Internet and by personal com-munication. The empirical part includes interviews from export assistants and a ship-ping operator. The empirical section describes the bill of lading difficulties in detail and provides the case company with different resolutions. The research findings show, that the majority of the problems in the use of bills of lading are caused by the shipping liner’s systems. Because of these systems, the drafts sometimes include an endless amount of mistakes, which are troublesome to correct over and over again. However, this research shows that there are some im-provements that Norilsk can make to enhance the situation. In the end of this thesis I have presented some solutions from which the company can choose the most suitable ones for them. Tämän opinnäytetyön tarkoituksena oli tutkia vaikeuksia liittyen erääseen merikulje-tusasiakirjaan, konossementtiin. Tutkimus toteutettiin Norilsk Nickel Harjavalta Oy:lle, joka on suuri ja kansainvälinen metalliteollisuudessa toimiva yritys. Norilsk Nickel halusi minun selvittävän, olisiko olemassa jotain tapoja vähentää konosse-menttien käytössä esiintyviä vaikeuksia ja etenkin konossementtiluonnoksiin liittyviä vaikeuksia. Norilsk Nickelillä oli ollut ongelmia konossementtiluonnosten kanssa jo pidemmän aikaa ja yrityksen mielestä oli aika selvittää ongelmat, sillä ne aiheuttivat ylimääräistä työtä ja siitä johtuen ylimääräisiä kustannuksia. Minun tehtävänäni oli tarjota yritykselle erilaisia tapoja hallita ongelmia ja ratkaista niitä. Valitsin tämän aiheen, sillä Norilsk Nickel tarjosi sitä minulle ollessani työharjoitte-lussa yrityksessä. Olin huomannut samoja ongelmia konossementeissa työni kautta ja olin todella kiinnostunut asiasta. Halusin oppia lisää konossementeista ja samalla aut-taa kollegoitani ja Norilsk Nickeliä ongelmien kanssa. Nämä vaikeudet veivät aikaa ja resursseja useammalta osapuolelta ja yritys tarvitsi ratkaisuja, jotka vähentäisivät työmäärää. Tämä tutkimus toteutettiin kvalitatiivisena tutkimuksena. Teoriaosiossa olen tutkinut yleisiä vientidokumentteja ja konossementteja yleisellä tasolla. Tämän lisäksi olen kertonut erilaisista konossementeista ja niiden käytöstä. Teoriaosion tieto on kerätty kirjoista, Internetistä ja henkilökohtaisten keskustelujen avulla. Empiirinen osio si-sältää haastattelut sekä vientiassistenteilta että laivausoperaattorilta. Kyseinen osio kuvaa konossementteihin liittyviä vaikeuksia yksityiskohtaisesti ja tarjoaa case-yritykselle erilaisia ratkaisuja. Tutkimustulokset osoittavat, että valtaosa konossementtien ongelmista johtuu varus-tamon käyttämistä järjestelmistä. Näiden järjestelmien takia konossementtiluonnokset sisältävät joskus loputtoman määrän virheitä, joita on työlästä korjata uudelleen ja uudelleen. Tämä tutkimus osoittaa kuitenkin, että myös Norilsk voi tehdä parannuk-sia, jotka kohentavat tilannetta. Opinnäytetyön lopussa olen esittänyt joitakin ratkai-suja, joista yritys voi valita heille sopivimman.